Catumaxomab for the Treatment of Malignant Ascites in Patients With Chemotherapy-Refractory Ovarian Cancer: A Phase II Study. Issue 9 (1st November 2014) - Berek, Jonathan S.; Edwards, Robert P.; Parker, Lynn P.; DeMars, Leslie R.; Herzog, Thomas J.; Lentz, Samuel S.; Morris, Robert T.; Akerley, Wallace L.; Holloway, Robert W.; Method, Michael W.; Plaxe, Steven C.; Walker, Joan L.; et al.
Abstract : Objective: The aim of this study was to investigate the efficacy and safety of intraperitoneal catumaxomab in heavily pretreated patients with chemotherapy-refractory ovarian cancer and recurrent symptomatic malignant ascites. Methods: The study is a single-arm open-label multicenter US phase II study. Patients received 4 three-hour intraperitoneal catumaxomab infusions (10, 20, 50, and 150 μg within 10 days). The primary end point was the percentage of patients with at least a 4-fold increase in the puncture-free interval (PuFI) relative to the pretreatment interval. The main secondary end points were puncture-free survival, overall survival, ascites symptoms, and safety. Time to first therapeutic puncture (TTPu) was analyzed post hoc. Results: Forty patients were screened, and 32 patients (80%) were treated. Seven patients (23%) achieved the primary end point. The median PuFI was prolonged 2-fold from 12 to 27.5 days. The median TTPu was prolonged 4-fold from 12 to 52 days. The median puncture-free survival and overall survival were 29.5 and 111 days, respectively. Nineteen patients (59%) required puncture after catumaxomab treatment. Ascites symptoms improved in most of the 13 predefined categories. At study end, most symptoms were still improved compared with screening. The most frequent treatment-related adverse events were related to cytokine release (vomiting, nausea, pyrexia, fatigue, and chills) or intraperitoneal administration (abdominal pain). Transient increases in liver parameters and transient decreases in blood lymphocytes were regularly observed but were generally without clinical relevance. Conclusions: Catumaxomab prolonged PuFI and TTPu had a beneficial effect on quality of life, as shown by the improvement in ascites symptoms, and had an acceptable safety profile, which is consistent with its mode of action.